RARE-58. CONGENITAL METASTATIC CHORDOMA OF THE CLIVUS. (4th December 2020) - Grajowska, Wieslawa; Stepaniuk, Maria; Trubicka, Joanna; Wójcicka-Kowalczyk, Katarzyna; Krych, Piotr; Dembowska-Baginska, Bozenna; Perek-Polnik, Marta
Abstract: Chordomas are rare midline axial skeletal neoplasms that typically present in adults. They are infrequent in childhood with typical localization in the spheno-occipital skull base. They are derived from remnants of the embryonic notochord. We present the case of 4 months old girl, who was born with „blueberry muffin" syndrome and was first negatively diagnosed for neuroblastoma and leukemia (two negative skin biopsies were performed) was admitted with axial laxity. In imaging testes there was a tumor of the scull base, metastases in the lungs and kidneys (that were not seen at previous assessments) and a small lesion in the heart. The third biopsy of skin lesion was performed and pathological examination revealed a neoplasm composed of cords, clusters, and chains of multivacuolated cells embedded within a myxoid matrix and separated by fibrous septa. No atypical and dedifferentiated features were present. Mitotic activity was not observed. Neoplastic cells showed the typical cytoplasmic immunostaining for EMA, S100 and cytokeratin AE1/AE3, strong nuclear brachyury expression, and retention of nuclear INI-1 expression. The diagnosis of chordoma was established. Neoplastic tissue and blood samples were obtained for molecular analysis using next generation sequencing, including germline mutations assessment (are ongoing). Chemotherapy as for soft tissue sarcomas was undertaken. Currently a patient is on treatment with improvement of neurological status.